5-Methylcytosine is not a mutation hot spot in nondividing Escherichia coli - Lieb, Margaret (The National Academy of Sciences of the USA, 1997)
Spontaneous deamination of 5-methylcytosine (5meC) causes hot spots of C·G → T·A mutations in Escherichia coli and in human cells. In E. coli, the resulting T·G mispairs can be corrected to C·G by very short patch (VSP) repair, which requires the product of gene vsr. Mutation hot spots in genes of replicating vsr(+) bacteria are attributable to low Vsr activity. To determine the rate of deamination of 5meC and the efficiency of VSP repair in nondividing bacteria, we used kanamycin-sensitive (Kan(S)) lysogens containing a λkan(−) prophage. Deamination of a 5meC in the kan(−) gene resulted in mutation to kanamycin resistance (Kan(R)). Lysogens containing a single λkan(−) prophage per bacterial genome were grown in synthetic medium with limiting amino acids and stored at 15°C or 37°C. In the absence of VSP repair, Kan(R) mutants accumulated at the rate of approximately 1.3 × 10(−7) per bacterium per day at 37°C. This is similar to the 5meC → T mutation rate reported for DNA in solution. In vsr(+) bacteria, the Kan(R) accumulation rate was 3 × 10(−9) per bacterium per day, which is not significantly higher than the rate observed when the target cytosine was unmethylated. The increase in Kan(R) mutants was barely detectable in vsr(+) cultures stored at 15°C for 4 months. It is likely that mutation hot spots at 5meC in rapidly dividing cells are attributable to insufficient time for T·G correction in the interval between deamination of 5meC and subsequent DNA replication. DNA synthesis occurred in bacteria starved for amino acids and this synthesis was not highly mutagenic.